Nitrogen Control of Atrazine Utilization in Pseudomonas sp. Strain ADP - García-González, Vicente (American Society for Microbiology, 2003)
Pseudomonas sp. strain ADP uses the herbicide atrazine as the sole nitrogen source. We have devised a simple atrazine degradation assay to determine the effect of other nitrogen sources on the atrazine degradation pathway. The atrazine degradation rate was greatly decreased in cells grown on nitrogen sources that support rapid growth of Pseudomonas sp. strain ADP compared to cells cultivated on growth-limiting nitrogen sources. The presence of atrazine in addition to the nitrogen sources did not stimulate degradation. High degradation rates obtained in the presence of ammonium plus the glutamine synthetase inhibitor MSX and also with an Nas(−) mutant derivative grown on nitrate suggest that nitrogen regulation operates by sensing intracellular levels of some key nitrogen-containing metabolite. Nitrate amendment in soil microcosms resulted in decreased atrazine mineralization by the wild-type strain but not by the Nas(−) mutant. This suggests that, although nitrogen repression of the atrazine catabolic pathway may have a strong impact on atrazine biodegradation in nitrogen-fertilized soils, the use of selected mutant variants may contribute to overcoming this limitation.